Secure true random number generator in WLAN/LAN - Chefranov, Alexander G.; Alavi Abhari, Seyed Masoud; Alavizadeh, Hooman; Zanjani, Maryam Farajzadeh (Association for Computing Machinery acmhelp@acm.org, 2013)
Wireless networks need more security in comparison to the other networks due to their intrinsic vulnerabilities to possible attacks. It is expected that by using a distributed method for true random number generators (TRNG) in wireless sensor networks (WSN) and wireless LAN (WLAN) randomness quality of generated numbers can be enhanced. We analyze a protocol for a distributed TRNG named ScatterLight(L.R. Giuseppe, M. Fabrizio and O. Marco, 2011) for a WSN. After making some changes on ScatterLightstructure and physical data sources, the Enhanced ScatterLightprotocol is introduced; it provides secure and high qualified true random numbers. Thus, the quality of randomness of obtained random numbers using National Institute of Standards and Technology tests is evaluated. Finally, by analyzing the results, it can be conducted that Enhanced ScatterLightprotocol in comparisons with ScatterLightprotocol in WLAN and LAN provides 60% and 53% better randomness quality respectively, while the performance is equal in both protocols. Copyright © 2013 ACM.
6th International Conference on Security of Information and Networks, SIN 2013 --
Keywords: Cryptography; Key generation; Network security; Nonce; True random numbers generator (TRNG)